Late life psychotic features in prodromal Parkinson's disease. (May 2021) - Pachi, Ioanna; Maraki, Maria I.; Giagkou, Nikolaos; Kosmidis, Mary H.; Yannakoulia, Mary; Dardiotis, Efthimios; Hadjigeorgiou, Georgios; Sakka, Paraskevi; Ntanasi, Eva; Xiromerisiou, Georgia; Stamelou, Maria; Scarmeas, Nikolaos; et al.
Abstract: Introduction: Some case series have suggested that psychotic features could occur even before the onset of motor symptoms of Parkinson's Disease (PD). Our aim was to investigate a possible association between psychotic symptoms and prodromal Parkinson's disease in a population-based cohort, the Hellenic Longitudinal Investigation of Aging and Diet study. Methods: This cross-sectional study included participants aged ≥65 years without dementia or PD. We defined psychotic symptoms as the presence of at least one new hallucinatory or delusional feature, assessed with the Neuropsychiatric Inventory scale and the Columbia University Scale for Psychopathology in Alzheimer's Disease, exhibited only at follow-up and not present at baseline visit. We calculated the probability of prodromal PD (pPD) for every participant, according to the 2019 International Parkinson and Movement Disorders Society research criteria for prodromal PD. Results: Participants who developed psychotic manifestations over a three-year follow up (20 of 914) had 1.3 times higher probability of pPD score (β [95%CI]: 1.3 [0.9-1.5], p=0.006) compared to non-psychotic subjects. This association was driven mostly by depressive symptoms, constipation and subthreshold parkinsonism (p<0.05). Conclusion: Our data indicate that emerging psychotic features evolve in parallel with the probability of pPD. This is the first study that provides evidence for the presence of psychotic experiences in pPD. The association detected needs to be confirmed in longitudinal studies. Highlights: Higher risk for possible prodromal Parkinson's disease in subjects with psychotic symptoms. Parallel progress of psychotic features and prodromal stage of Parkinson's disease. Depression, constipation and parkinsonism are the main mediators.